The Effect of Jaundice on Some Hematological and Biochemical Parameteres in Human - Maulood, K. A; Amin, I. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study has investigated the effect of jaundice on some hematological and biochemical paramenters in male and female. The results have shown significant decrease in Hemoglobin concentration, packed cell volume, white blood cell count and platelet count. The biochemical parameters results have shown significant increase in prothrombine time, level of total bilirubin, Aspartale transminase and Alanin trans aminase in the serum of male and femal.